Critical care handbook of the Massachusetts General Hospital - Bigatello, Luca M.; Alam, Hasan B.; Allain, Rae M.; Bittner, Edward A.; Hess, Dean R.; Pino, Richard M.; Schmidt, Ulrich (A Lippincott Williams & Wilkins handbook, 2010)
Written by the multidisciplinary intensive care unit staff at the Massachusetts General Hospital, the Fifth Edition of this best-selling handbook is a practical, complete, and current guide to medical and surgical critical care. In a user-friendly outline format designed for rapid reference, this pocket-sized book presents reliable, hospital-tested protocols that reflect today's most advanced critical care practices. This edition includes new chapters on disaster preparedness in the ICU, quality improvement and prophylaxis, non-antibiotic therapies for sepsis, and use of ultrasound in the ICU. An appendix provides supplemental drug information.